Coronary flow capacity: concept, promises, and challenges - van de Hoef, Tim P. (Int J Cardiovasc Imaging, 2017)
The vasodilator capacity of the coronary circulation is an important diagnostic and prognostic characteristic, and its accurate assessment is therefore an important frontier. The coronary flow capacity (CFC) concept was introduced to overcome the limitations associated with the use of coronary flow reserve (CFR) for this purpose, which are related to the sensitivity of CFR to physiological alterations in systemic and coronary hemodynamics. CFC was developed from positron emission tomography, and was subsequently extrapolated to invasive coronary physiology. These studies suggest that CFC is a robust framework for the identification of clinically relevant coronary flow abnormalities, and improves identification of patients at risk for adverse events over the use of CFR alone. This Review will discuss the concept of CFC, its promises in the setting of ischaemic heart disease, and its challenges both in theoretical and practical terms.